Physical activity and body posture of younger school children in the opinion of parents - Anna Krystyna Makarczuk; Michał Kowalewski (Kazimierz Wielki University, 2020)
The research was conducted in 2017 - 2018 in Łódź among parents of children attending the classes I - III of primary school. The method of diagnostic survey was used and a total of 521 questionnaires were collected. The general level of parents' knowledge of the causes of posture defects and their prevention is low. Only twenty percent of parents can identify the most common causes of defects and factors that negatively affect a body posture. Among the studied population of children, body posture disorders occur in 83% of cases. Children most often do not perform corrective and compensatory exercises at home (73%) and do not attend corrective gymnastics (56%). A significant percentage of people (58%) spend five or more hours a day sitting and playing the computer. The percentage of children not participating in any additional physical activities is also relatively high (43%). These facts arise the request of the need to take action to increase awareness among parents for the prevention and treatment of static disorders of the body.